The Role of Motivation in Mediating Spiritual-Based Transformational Leadership Towards Employee Loyalty - Hidayah, Tamriatin; Prastyowati, Agustin Hari; Winahyu, Pawestri; Hassan, Zainudin (Jurnal Aplikasi Manajemen, 2026)
The goal of the current study is to examine how motivation functions as a mediating factor in the interaction between the loyalty of non-permanent employees at the Ministry of Cooperatives and SMEs and interpersonal Sharia-based Transformational Leadership, pay, and work environment. Purposive sampling was used to select 373 respondents from the study population, which included all non-permanent employees (PTT-PT/THL) at the Ministry of Cooperatives and SMEs. Smart PLS (Partial Least Squares-SEM) is used for data analysis in this quantitative study. The results of the study indicate that interpersonal Sharia-based Transformational Leadership significantly improves motivation even though it has no direct effect on loyalty. Motivation acts as a mediator between this and loyalty, which is then mediated by it. The results also show that, both directly and through motivation's mediating function, pay and the workplace have a significant positive impact on loyalty and motivation. This study has two practical implications: first, it highlights the significance of raising pay standards and establishing a positive work atmosphere; second, it highlights the need to develop spiritually oriented leadership in order to foster employee loyalty and motivation. This study makes a theoretical addition by examining how motivation mediates the link between these factors in the public sector and integrating spiritual principles into transformational leadership.